(untitled) (Balneo and PRM Research Journal, 2024)
In team handball, coaches can make unlimited substitutions, allowing players to enter the game at any time, even if they haven’t been active on the bench. The aim of this study was to investigate the impact of inactivity following a warm-up on the physical performance and physiological responses of female elite team handball players. The secondary aim of the study was to examine a possible connection between the examined parameters. Twelve female adult elite field handball players (n = 12; age, 31.9 ± 4.05 years; weight, 66.1 ± 5.8 kg; height 173 ± 3.8 cm and body mass index, 2.2 ± 0.2 kg/cm2) were examined. All tests were assessed in two distinct situations: (a) immediately after warm-up (T1-AW) and (b) after a 15-minute inactivity period (T2-IP). The physical tests performed were: countermovement jump with arms fixed (CMJ AF), squat jump (SJ), medicinal ball rotational throw test right (MBTT-R) and medicinal ball rotational throw test left (MBTT-L) and 10 m acceleration test (TA 10m). Heart rate (HR) was measured during warm-up and at T2-IP, while body temperature (BT), lactic acid (LA), serum glucose (G), and blood oxygen saturation (SpO2) were measured at T1-AW and T2-IP. Significant differences were found at T2-IP for RSI1 (t= 2.88, p < 0.01) and PP (t= 2.24, p < 0.05), specific to CMJ AF and RSI1 (t= 3.88, p < 0.01), and for PP specific to SJ (t= 2.28, p < 0.05). All physical indices correlated positively with the physiological ones. In addition, two significant correlations were identified, one between the decrease in the RSI 1-CMJ AF index and the PP-CMJ AF index (r=0.59, p<0.05) and another between the decline in the PP- SJ and Tc (r=0.60, p<0.05). The results obtained from the present study indicate that short-term inactivity can negate some of the physical and physiological benefits that players gain from warming up. The study revealed a significant reduction in certain parameters related to jump tests after a 15-minute period of inactivity. Moreover, it was observed that there is a direct correlation between the decrease in body temperature and the reduction in peak power specific to squat jump performance. This implies that lower body temperatures that result from a short period of inactivity can have a negative impact on jumping performance just before players enter the game. Keywords: female team handball, warm-up, inactivity, physical performances, physiological parameters.